Pengaruh Supporting Electrolyte untuk Deteksi Ion Logam Cd(II) dan Zn(II) menggunakan PLE Termodifikasi Lapisan Tipis Perak dengan Metode Voltametri - Fatimah As Sarah; Trisna Kumala Sari (MASALIQ, 2025)
Cd(II) and Zn(II) metal ions are toxic environmental contaminants that pose potential risks to human health, necessitating accurate and efficient detection methods. This study aims to optimize the supporting electrolyte conditions for the simultaneous electrochemical detection of Cd(II) and Zn(II) ions using a Pencil Lead Electrode (PLE) modified with a thin silver layer (Ag/PLE). Cyclic voltammetry was employed to evaluate the effectiveness of electrode modification and the influence of electrolyte variation on the detection sensitivity of both metal ions. Experimental results indicate that 0.1 M acetate buffer is the optimal supporting electrolyte, yielding an anodic potential (Epa) of –0.37 V and a peak current of 1.48 mA, as well as a cathodic potential (Epc) of –0.9140 V for Cd(II). For Zn(II), the Epa was observed at –0.79 V with a current of 0.54 mA and Epc at –0.6790 V. The difference in detection sensitivity between the two metal ions is attributed to variations in analyte diffusion rates at the electrode surface. These findings demonstrate that the Ag/PLE-based electrochemical approach offers a simple, sensitive, and cost-effective method for the simultaneous detection of heavy metal ions, contributing significantly to rapid and practical environmental monitoring systems.